SCHEDULING ANALYSIS USING THE PRECEDENCE DIAGRAM METHOD (PDM) METHOD IN THE PHASE II BRIDGE CONSTRUCTION PROJECT IN PEJAMBUAN VILLAGE, SUNGAI TABUK DISTRICT, BANJAR REGENCY, SOUTH KALIMANTAN - Pinanggi, Alfisyah Oktarina; Karim, Abdul; Widiastuti, Endah (CERUCUK, 2025)
In its implementation, starting from the planning stage, the implementation of scheduling, to the supervision and implementation of good controls, construction projects need to be well managed in their work. In the process of Building the Phase II Bridge Project in Pejambuan Village, Sungai Tabuk District, there was a slight delay in the eighth week due to equipment damage and delays in the material supply mobilization process. This project only has a time schedule in the form of an S Curve which is not helpful in controlling work in the field.This study aims to analyze scheduling using  the Precedence Diagram Method (PDM) method assisted by the Microsoft Project 2021 application and identify critical and non-critical paths of work so that the implementation of the project can be carried out with an effective duration.Based on the results of the analysis of this study, the total duration of work is 138 working days with the total duration of work calculated using calendar days for 174 days, and the total duration of project realization is 180 calendar days. CV planning calculation. Al Fatih Karya is scheduled to be completed by September 30, 2024, while scheduling with the PDM method is completed by September 24, 2024. The critical trajectory in the results of this analysis is found in 13 activities starting from ordinary excavation work and ending with the installation of bridge nameplates. Keywords : Bridge, Microsoft Project 2021, Scheduling, Delay, PDM